80 years of the School of Public Health of the University of Chile. A personal historical view - Solimano C., Giorgio (Revista Chilena de Salud Pública, 2023)
This article presents notable aspects of the evolution of the School of Public Health “Dr. Salvador Allende G.” at the University of Chile since its creation in 1943 from a personal historical perspective. The School made significant academic progress and became a national leader in Latin America from that date until September 1973. From 1973 to 1999, the military dictatorship directed the organization with military officers and a public health physician. This reduced its presence in Chile and internationally while maintaining its core activities. The School has made significant progress since the turn of the century, highlighted by the creation of the Doctorate in Public Health in 2003, reform of master’s programs, strengthened academic and professional body, innovative program planning and management, and renewed international presence in Latin America and globally.